Crafting normalcy : how communication enhances tourist village’s resilience during the Covid-19 pandemic - Rahmanto, Andre N. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Covid-19 pandemic has resulted in a multisectoral crisis, including tourism which is the most affected sector. Like other tourist destinations, the tourist villages are also forced to close all their activities. Inevitably, they have suffered many losses, and thousands of residents have lost their jobs. But in the midst of uncertainty, the tourist villages still have a way to survive and show resilience. Resilience both individually and organisationally will always be formed in and through communicative processes that enhance the ability to create a new normal. The important issue is how communication can improve the resilience of individuals and groups of rural tourism actors during the Covid-19 pandemic. This research was conducted in Nglanggeran Village, Yogyakarta. Yogyakarta is one of the priority tourism destinations in Indonesia and now has around 150 tourist villages. By using Buzzanell’s communication theory of resilience framework, the data of the research were collected through in-depth interviewing with a number of tourist village actors in Nglanggeran Village, Yogyakarta Province. They were analysed by using Creswell's data analysis spiral, consisting of reading-memoing, describing-classifying, interpreting, and representing-visualising stages. The results of this study show that communication plays an important role in supporting resilience of Nglanggeran tourism village actors during the Covid-19 pandemic. Five aspects of resilience communication are found in the three stages of the pandemic disaster.